Process optimization of a cereal-based fermented beverage (Boza) powder and investigating upscaling conditions - Gul, Osman; Atalar, Ilyas; Tornuk, Fatih; Akgun, Abdullah (WILEY, 2023)
Boza is a traditional fermented cereal-based beverage, which should be consumed within 3-5days after production due to its short shelf-life. Spray drying process is an excellent option to overcome this problem to make the product least perishable. The optimal spray drying conditions for boza powder production in a laboratory-scale spray dryer were investigated using, Response Surface Methodology. Air inlet temperature and feed flow rate were the main parameters that affected the responses such as powder yield, moisture content, cell viability, particle size, and solubility. The optimum spray drying conditions were 148 degrees C air inlet temperature, 9 degrees C feed temperature, and 10 ml/min feed flow rate. At these optimum conditions, deviations between predictive and experimental values were found very low. A 1.5 log cfu/g reduction in lactic acid bacteria (LAB) viability was achieved, however instant properties of boza powder should be improved by agglomeration processes. Laboratory and pilot scales were also compared at the determined optimum drying conditions. Approximately 0.4 log cfu/g difference in LAB viability was observed between the two scales. Practical ApplicationsBoza is one of the most valuable fermented cereal products due to its high nutritional value. The short shelf life of Boza limits its consumption and makes it a seasonal product. Spray drying technology could provide overcome these challenges and improve the usability and durability of boza beverages. However, the quality of a spray-dried product highly depends on process conditions. Therefore the effects of the spray drying process conditions on the physicochemical properties of boza powder and the scale-up conditions were investigated for the first time in this study.
Keywords: Boza drying; mathematical modeling; powder technology; scale-up process; spray drying; SPRAY-DRYING PROCESS; BED AGGLOMERATION; TEMPERATURE; PROBIOTICS; SOURDOUGH; VIABILITY; SURVIVAL; STARTER; YOGURT; Engineering; Food Science & Technology